EVALUASI KINERJA OPERASIONAL TERMINAL DARA KOTA BIMA - SUTEJA, I WAYAN; ROHANI, ROHANI; HASYIM, HASYIM (Universitas Mahasaraswati Mataram, 2020)
Terminal Dara is the center of community activities in meeting the needs for movement from one place to another with various purposes used by the people of the of Bima City and Regency. Terminal Dara has experienced a decline and an increase in the number of transportation from year to year; this condition makes facilities and operational performance at the Dara Terminal become very important. The purpose of this study is to determine the operational performance and facilities as well as the current area of Dara Terminal facilities. The method used in this study is a direct survey in the field for primary data by recording the bus license plate, time of entry and exit of buses and visitors vehicles at the entrance and exit gate and recording the number of passengers and users of waiting rooms, the number of seats in passenger waiting rooms, and bus station facilities. Data collection is carried out for three days with duration of 13 hours each day.Based on the results of the analysis of the performance that has been carried out, the value for the bus queue analysis ? = 2.11> 1 indicates that there is a queue of bus services at Dara bus station. The highest value of arrival average time headway is 17 minutes 22 seconds and the departures average time headway is 12 minutes 23 seconds. The highest departure load factor is 81.44% in the ANGDES and the highest load factor is 73.64% in ANGDES too. The parking space requirement for cars and motorbikes of 128 m² can still be served by vehicle parking area in bus station, while the parking area for bus is not able to serve bus which parked in the bus parking area with the value of parking space needs 902.5 m² while the area the current bus parking area is 631.25 m². Based on the results of the performance analysis that has been done, the value obtained for bus queue analysis ? = 2.11> 1 indicates that there is a queue of bus services in Dara Terminal. The time between the highest average arrivals is 17 minutes 22 seconds and the time between the highest average departures is 12 minutes 23 seconds. The highest departure load factor was 81.44% at ANGDES and the highest arrival load factor was 73.64% at ANGDES as well. The need for parking spaces for private cars and motorbikes of 128 m² can still be served by the terminal private vehicle parking area, while the parking area for buses is not able to serve buses that park in the bus parking area with a value of 902.5 m² of parking space while the area the bus parking area is currently 631.25 m². Based on existing survey results, the bus departure lane and passenger lounge of Terminal Daral need to be renovated, or they can relocate the terminal to a wider area.